2020
DOI: 10.1002/jor.24652
|View full text |Cite
|
Sign up to set email alerts
|

Operative and nonoperative management of anterior cruciate ligament injury: Differences in gait biomechanics at 5 years

Abstract: Gait biomechanics after anterior cruciate ligament (ACL) injury are associated with functional outcomes and the development of posttraumatic knee osteoarthritis. However, biomechanical outcomes between patients treated nonoperatively compared with operatively are not well understood. The primary purpose of this study was to compare knee joint contact forces, angles, and moments during loading response of gait between individuals treated with operative compared with nonoperative management at 5 years after ACL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 53 publications
1
15
1
Order By: Relevance
“…Although arthroscopic assessments in the current work were collected on some knees still in an acute injury phase, cartilage compositional changes were assessed exclusively after surgery, as the baseline MRI here was acquired 6 weeks after ACLR. That subtle difference is relevant to understanding the evolution of pre-OA following ACLR, specifically in the postsurgical knee where cartilage is exposed to a different mechanical 27,32,33 and biological environment [34][35][36][37] compared with freshly injured and unreconstructed joints. Although the longitudinal cartilage T2 increases observed in this study occurred in the context of the postsurgical joint, effects of the initial injury contribute to the sum total of the post-ACLR environment.…”
Section: Discussionmentioning
confidence: 99%
“…Although arthroscopic assessments in the current work were collected on some knees still in an acute injury phase, cartilage compositional changes were assessed exclusively after surgery, as the baseline MRI here was acquired 6 weeks after ACLR. That subtle difference is relevant to understanding the evolution of pre-OA following ACLR, specifically in the postsurgical knee where cartilage is exposed to a different mechanical 27,32,33 and biological environment [34][35][36][37] compared with freshly injured and unreconstructed joints. Although the longitudinal cartilage T2 increases observed in this study occurred in the context of the postsurgical joint, effects of the initial injury contribute to the sum total of the post-ACLR environment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in previous studies that the gait pattern may affect following ACL injuries [ 4 6 ]. The ACL injury may result in loss of knee joint stability and abnormal movement patterns, leading to the early development of degenerative changes such as osteoarthritis of the knee joint [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Button et al [ 14 ] reported no difference in sagittal plane knee angle and movements in patients who undergone ACL rehabilitation compared to healthy controls. According to Khandha et al [ 4 ], the patient who received rehabilitation protocol following ACL injury walked with 28% greater medial compartment contact forces and 28% greater peak knee adduction moment in the involved knee compared with patients who have undergone ACL reconstruction surgery. Even though there are several studies available in the literature about the changes in gait kinematics following ACL injury and ACL reconstruction surgery [ 11 , 15 ], none of these studies investigated the changes in gait kinematics following nonoperative ACL rehabilitation protocol.…”
Section: Introductionmentioning
confidence: 99%
“…ACL, a ligament directly connecting the femur to the tibia, stabilizes the knee joint in the anterior-to-posterior direction, prevents anterior-tibial subluxation, as well as provides rotational stability. A sudden turn or noncontact mechanism typically causes an ACL tear resulting in knee subluxation, pivot shift, and joint instability indicated in altered joint kinematics and gait patterns [21][22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%